1994
DOI: 10.1161/01.cir.90.4.1908
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-induced vascular smooth muscle cell proliferation is modulated by the growth amplification factors serotonin and adenosine diphosphate.

Abstract: Background Platelet-mediated mechanisms have been implicated in intimal lesion formation following vascular injury. Although the participation of peptide growth factors has been suspected in this process, little has been known about the possible mitogenic role of other platelet factors that are released at sites of vascular injury.Methods and Results We tested the hypothesis that platelet products, which are not peptide growth factors, are important modulators of the platelet-induced smooth muscle cell (SMC) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 40 publications
0
47
0
3
Order By: Relevance
“…34 Extracellular ATP and ADP released from platelets, as well as injured or activated SMCs and endothelial cells, is mitogenic for intimal SMCs via P2Y receptors 35 and synergistically acts with growth factors such as plateletderived growth factor and basic fibroblast growth factor. 35,36 The neointima in the present study was exclusively composed of SMCs and extracellular matrix, suggesting that increased NTPDase activity on SMCs suppresses neointimal growth via the inhibition of SMC proliferation. In addition, thrombus itself contributes to neointimal formation and plaque progression.…”
Section: Furukoji Et Al Placental E-ntpdase Suppresses Thrombosismentioning
confidence: 57%
“…34 Extracellular ATP and ADP released from platelets, as well as injured or activated SMCs and endothelial cells, is mitogenic for intimal SMCs via P2Y receptors 35 and synergistically acts with growth factors such as plateletderived growth factor and basic fibroblast growth factor. 35,36 The neointima in the present study was exclusively composed of SMCs and extracellular matrix, suggesting that increased NTPDase activity on SMCs suppresses neointimal growth via the inhibition of SMC proliferation. In addition, thrombus itself contributes to neointimal formation and plaque progression.…”
Section: Furukoji Et Al Placental E-ntpdase Suppresses Thrombosismentioning
confidence: 57%
“…5-HT not only interacts synergistically with platelet-derived growth factor 4 but also has a direct mitogenic effect on cultured aortic VSMCs. [3][4][5]25,26 It has also been reported that 5-HT stimulates the expression of thrombin receptors in VSMCs probably by 5-HT 2 receptors, which would further potentiate the contraction and proliferation of VSMCs by thrombin. 27 These effects could cause narrowing of the vessel lumen and contribute to both the development of atherosclerosis and the restenosis observed after angioplasty.…”
Section: Discussionmentioning
confidence: 94%
“…Vasoconstriction, together with platelet aggregation, would reduce arterial blood flow and would increase the risk of thrombus formation. 24 5-HT also promotes the proliferation [3][4][5] and migration of VSMCs 6 and may contribute to the progression of atherosclerosis, which is considered to be the major risk factor of arterial thrombotic disease. 5-HT not only interacts synergistically with platelet-derived growth factor 4 but also has a direct mitogenic effect on cultured aortic VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present study suggests that serotonergic mechanisms do not operate through increased PA among smokers, local vascular mechanisms may come into play, such as vasoconstriction in response to serotonin release, 39 -40 and smooth muscle cell proliferation. 41 Such mechanisms could be the focus of future research in this area.…”
Section: Discussionmentioning
confidence: 99%